Crashworthiness Performance Study of 3D-Printed Multi-Cell Tubes Hybridized with Aluminum Under Axial Quasi-Static Testing - Ardiansyah, Riki; Indriani, Fitri Karina; Hidayat, Dony; Tjahjono, Arif; Nurrohmad, Abian; Marta, Aryandi (Automotive Laboratory of Universitas Muhammadiyah Magelang in collaboration with Association of Indonesian Vocational Educators (AIVE), 2024)
This study investigates the crashworthiness performance of 3D-printed hybrid tubes, fabricated using PLA and PACF filaments with varying shell thicknesses (1, 1.5, and 2 mm). The hybrid tubes, composed of a shell, aluminum, and multi-cell structure, were subjected to axial quasi-static testing. Results indicate that both shell thickness and filament type significantly influence crashworthiness. PLA specimens with a shell thickness of 2 mm absorbed 504 J of energy, whereas PACF specimens with the same thickness absorbed only 342.9 J. The deformation mode analysis revealed mixed deformation patterns, including diamond, fracture, and fragmented modes. The study also evaluated specific energy absorption (SEA) and crushing force efficiency (CFE). The PLA specimen with a 2 mm shell thickness exhibited the highest SEA value of 18.61 J/g among all specimens. In contrast, the PACF specimen with the same shell thickness demonstrated the highest CFE value of 0.82 among the tested specimens. Overall, this research contributes insights into the design optimization of 3D-printed hybrid tubes for enhanced crashworthiness.